Modelo fenomenológico para compressores alternativos - Willian Moreira Duarte (2014)
This paper presents the development of a mathematical model of a reciprocating compressor operating at steady state, implemented in the computer program Engineering Equation Solver (EES). The main input variables of the model are the pressure and temperature in the suction, the discharge pressure and the rotation of the compressor. The main output variables are the flow rate and the temperature at the compressor discharge. To develop the model, the compressor was divided into three control volumes: the region of pre-compression, the compression chamber and the post-compression region. In the compression chamber, are considered thermals and hydraulics aspects of the flow of the refrigerant, while the other two volumes of control are quantifed the thermal phenomena. The model was validated experimentally using an open compressor is R134a, operating with different suction pressures and discharge and with different rotational speeds. The validation of the model was successfully performed, comparing the mass flow rate and the discharge temperature generated by the model with the values of these quantities obtained experimentally. These quantities and their uncertainties were compared using a confidence interval of 95.45%. The result of mass flow rate has the same quality of experimental result because the uncertainty of the mass flow rate obtained by the model was of the same order of magnitude of the uncertainty of the measured flow. The model was also used to evaluate the performance of the compressor, for various points tested. The model was further employed to simulate the performance of the compressor clearance volume for changes in the equipment.